2010
DOI: 10.1007/s00405-010-1315-y
|View full text |Cite
|
Sign up to set email alerts
|

CO2 laser-assisted microsurgery for intracordal cysts: technique and results of 49 patients

Abstract: Microsurgery for intracordal cysts is a challenging procedure, because cysts are close to the vocal ligament and the risk of inducing a scar is high. In this retrospective study, our experience with the CO(2)-laser scanning system (Acublade(®)) is reported on 49 patients. There were 41% epidermoid cysts and 59% mucous retention cysts. A quarter of the patients presented with bilateral cystic lesions and 59% had a contralateral lesion other than a cyst. The cyst was removed after a minimicroflap. It was dissect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…This may be performed with cold instruments or with laser technology, which is increasingly well evidenced. 60 With the flap retracted medially, the cyst is completely removed. The flap is then replaced and may be held in place with fibrin sealant or microsutures or left to heal naturally.…”
Section: Key Findingsmentioning
confidence: 99%
“…This may be performed with cold instruments or with laser technology, which is increasingly well evidenced. 60 With the flap retracted medially, the cyst is completely removed. The flap is then replaced and may be held in place with fibrin sealant or microsutures or left to heal naturally.…”
Section: Key Findingsmentioning
confidence: 99%
“…These include conservative methods such as marsupialization, wide‐opening method, subepithelial infusion technique, island flap technique, and CO 2 laser‐assisted microsurgery. However, none have been shown to have outstanding clinical efficacy 3–7 . Since 2012, we have been using the “cotton ball self‐retraction” technique in vocal cysts surgeries.…”
Section: Introductionmentioning
confidence: 99%
“…However, none have been shown to have outstanding clinical efficacy. [3][4][5][6][7] Since 2012, we have been using the "cotton ball self-retraction" technique in vocal cysts surgeries. In a previous study, we reported that this surgical technique is feasible as a supportive surgical method during the microflap technique.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, fibrotic bands remain attached to overlying epithelium or an underlying vocal ligament after microflap dissection, and this can result in recurrence and persisting dysphonia . Given these consideration, various more effective and conservative surgical techniques have been developed such as marsupialization, the wide‐opening method, the subepithelial infusion technique, the island flap technique, and CO 2 laser–assisted microsurgery . Various surgical techniques are used to reduce the possibility of rupture and damage of vocal epithelium.…”
Section: Introductionmentioning
confidence: 99%